Transforming into a Swallow: Coffin Text Spell 294 and Avian Behaviour - Cooper, Julien (Zeitschrift für ägyptische Sprache und Altertumskunde, 2015)
Coffin Texts Spell 294 describes the transformation of the deceased into a mn.t -bird. Examination of the passage from a lexical, mythological, and geographical perspective have highlighted the bird’s solar and Hathoric associations, but additional layers of meaning are revealed when textual references are also examined zoologically. This approach has shown that Spell 294 accurately describes the appearance and natural behaviour of migratory and resident barn swallows (Hirundo rustica), elucidating formerly problematical allusions and leading to a deeper understanding of the spell’s transformative process.